Mujeres terribles (Heroínas de la mitología griega I) - Esteban Santos, Alicia (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2005)
After listing greek heroines in different positions either as passive victims or as rebel and active women, this paper focuses on the latter and takes the most representative of them –Medea and Clytemnestra (and her daughter Electra)– as an exemple. We talk about their relation and confrontation with the respective husband, whose personality is weaker and more negative than hers, and specially about the comparison between Medea’s story and Clytemnestra`s, with analogies and mainly contrasts.